Mineral Nutrition of Nutmeg (Myristica Fragrans Hout.) in relation to Deficiency Symptoms and flowering - Joseph Philip (Department of Plantation Crops and Spices, College of Horticulture, 1986)
Detailed investigations were carried out at the College of Horticulture, Kerala Agricultural University, Vellanikkara from 1982 to 1985 with a view to study the nutrient deficiency symptoms by inducing deficiency and to study the influence of carbohydrates, nutrient elements and their ratios on flowering of nutmeg. Deficiency symptoms of macro-nutrients except Ca and S were first manifested on the older leaves while that of micro-nutrients on younger leaves. Symptoms of N deficiency were expressed as yellowing of leaves with orange tinge except the midrib and lateral veins followed by development of brownish necrotic blotches with bright orange yellow halos. Bronze green to purple discolouration of leaves with purplish brown necrotic blotches were the symptoms of P deficiency. Potassium deficiency symptoms were characterized by chocolate brown necrosis along the leaf tip and margins which later progressed to the distal one third to two third portion of the laminae. Due to Ca deficiency, the younger leaves became thick, brittle and reduced in size with blunt end. Light orange yellow chlorosis developed along the leaf margins and tips followed by the development of necrotic spots with bright orange yellow zone adjacent to the necrotic areas. Magnesium deficiency was characterized by the yellowing of the midrib and lateral veins and adjacent areas starting from the base of the leaf followed by yellowing of the entire laminae, necrosis and outward cupping of margins. In the case of S deficiency, the younger leaves became uniformly lemon yellow which later developed characteristic ‘birds eye spot’ and ‘shot holes’. Interveinal chlorosis of the young leaves was the most commonly observed symptom of micro-nutrient deficiencies. However, the chlorosis was specific to the concerned nutrients. Uniform straw yellow discoloration of leaves with pale green midrib and lateral veins followed by development of necrosis from leaf tip towards base, downward cupping of leaves and asymmetrical laminae were the symptoms of Fe deficiency. Manganese deficiency symptoms were characterized by pale yellow interveinal chlorosis and crinkling of leaves. Development of water-soaked spots from margins and tips in a wavy pattern towards the midrib followed by downward cupping, coppery red necrosis and leaf distortion were the characterization symptom of Cu deficiency. Symptoms of Zn deficiency were expressed as abnormally long and narrow leaves with characteristic mottling and reduced internodes. Boron deficiency symptoms were expressed as crinkling and orange yellow chlorosis of leaf tip of younger leaves which were thick and brittle. Later on, bright orange yellow chlorotic patches developed in between the lateral veins followed by the development of necrosis from margins and tips at the distal portion. Cracks developed at the necrotic areas and torn off. Among the macro and micro-nutrients, the earliest deficiency symptoms were manifested by the element Fe (3rd month), followed by Mg and S (4th month) N (5th month) P and B (7th month), K, Cu and Zn (8th month), Ca (9th month) and Mn (9.5th month). Vegetative growth was markedly reduced due to the deficiency of macro and micro-nutrients. Calcium, P, K, Mg and Zn were the elements which showed profound influence on root growth. The growth of plant was found to be completely arrested at a comparatively early stage (5th month) due to Mg, S and Fe deficiencies, followed by B (7th month), N (9th month), P, K, Ca, Cu an Zn (10th month) and Mn (10.5th month) deficiencies. Visual symptoms of deficiencies were concurred with a marked reduction in the foliar level of the concerned element. The influences of macro and micro-nutrient deficiencies on the foliar level of other nutrients are furnished below. Comparative foliar concentration of nutrients Nutrient deficiency --------------------------------------------------------------------- Elements increased Elements decreased Nitrogen P, Zn, B Mg, Fe, Mn Phosphorus N, Zn Mg, Mn Potassium Ca, Mg Nil Calcium K, Mg, N B Magnesium Ca, K, Cu N Sulphur N, P Nil Iron P, Zn, Mn K, Ca Manganese Fe, K, N Nil Copper Fe, Mg Ca Zinc P, Fe Mg Boron N, P Ca, K The deficiency symptoms could be recovered by the application of the deficient nutrient element. The flowering shoots of nutmeg were found to be associated with a significantly higher concentration of carbohydrates in leaves. The flowered shoots had a relatively lower amount of N in leaves prior to flowering and the N content increased slightly towards flowering. It was observed that the P, K, Ca and Mg were higher in the flowering shoots. But the variation was significant only in the case of Ca and Mg, that too in three flushes out of the normal four. The flowering shoots had a relatively lower concentration of foliar S than that of the non-flowering shoots. The flowering shoots registered significantly higher C/N ratio in leaves than that of the non-flowering shoots. The flowered shoots always registered a relatively higher P/S, Ca/S and Mg/S ratios and a lower foliar level of Ca/Mg, N/P and N/K ratios. The flowered and non-flowered shoots showed an erratic trend with respect to K/Ca, K/P and Ca + Mg ratios. K